2012
DOI: 10.1152/jn.00660.2011
|View full text |Cite
|
Sign up to set email alerts
|

Diverse levels of an inwardly rectifying potassium conductance generate heterogeneous neuronal behavior in a population of dorsal cochlear nucleus pyramidal neurons

Abstract: Leao RM, Li S, Doiron B, Tzounopoulos T. Diverse levels of an inwardly rectifying potassium conductance generate heterogeneous neuronal behavior in a population of dorsal cochlear nucleus pyramidal neurons. J Neurophysiol 107: 3008 -3019, 2012. First published February 29, 2012 doi:10.1152/jn.00660.2011.-Homeostatic mechanisms maintain homogeneous neuronal behavior among neurons that exhibit substantial variability in the expression levels of their ionic conductances. In contrast, the mechanisms, which genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
96
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(114 citation statements)
references
References 54 publications
6
96
0
12
Order By: Relevance
“…Membrane potential in CsCl + bias current condition: −70.0±1.4 mV). The voltage-dependent drop in membrane resistance is likely due to activation of inward rectifier K + conductance, as described previously (Leao et al, 2012). In agreement with a HCN-mediated mechanism, CsCl blocked the AHP following aEPSPs (n=7, Figure 3A+inset).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Membrane potential in CsCl + bias current condition: −70.0±1.4 mV). The voltage-dependent drop in membrane resistance is likely due to activation of inward rectifier K + conductance, as described previously (Leao et al, 2012). In agreement with a HCN-mediated mechanism, CsCl blocked the AHP following aEPSPs (n=7, Figure 3A+inset).…”
Section: Resultsmentioning
confidence: 67%
“…Given that fusiform cells express a long-lasting Na + current that is active at subthreshold voltages (Leao et al, 2012), we hypothesized that subthreshold excitation might activate this current and broaden parallel fiber-fusiform cell EPSPs. If so, the slow inward component observed in stellate cells (Figure 1B) would not merely represent a passive depolarization of fusiform cell dendrites during EPSPs, but rather an active subthreshold depolarization by Na + currents in prejunctional fusiform cells.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained by Hirsch and Oertel (1988) in fusiform cells of the dorsal cochlear nucleus of mice where a TTXsensitive increase in R m with depolarization was observed. These authors also observed a concomitant decrease in R m and τ m with hyperpolarization, in parallel with the deactivation of I NaP which is present in these neurons (Leao et al 2012).…”
mentioning
confidence: 70%
“…Given that spontaneous firing of fusiform cells is dependent on their intrinsic ionic conductances (20), we blocked excitatory and inhibitory synaptic transmission to study the role of intrinsic conductances on the observed tinnitus-related DCN hyperactivity. Using whole-cell and cell-attached recordings in DCN slices, we recorded from fusiform cells in control, tinnitus, and nontinnitus mice 1 wk after noise exposure.…”
Section: Resultsmentioning
confidence: 99%